Fabrication of natural dye sensitized solar cell using tridax procumbens leaf and beetroot extract mixer as a sensitizer. (2022) - Arjun Kumar, B.; Ramalingam, G.; Karthigaimuthu, D.; Elangovan, T.; Vetrivelan, V.
Highlights: Eco friendly and natural abundant sources derived dyes were used as a sensitizer for dye sensitized solar cells. Chlorophyll and betalain dye pigment extracted from tridax procumbens leaf and beetroot, which was used as a sensitizer. The 1:1 ratio of Chlorophyll and betalain dye mixer shows better solar cell efficiency about 0.11% . Abstract: Chlorophyll and betalain dye pigment extracted from tridax procumbens leaf and beetroot, which was used as a sensitizer for natural dye sensitized solar cell (NDSSC). Titanium dioxide (TiO2 ) powder was synthesized by co-precipitation method with cetyltrimethylammonium bromide (CTAB) act as a surfactant. The prepared TiO2 sample was characterized by X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and UV–Vis absorption spectra to analysis the structural, morphological and optical properties studies were carried out. The as prepared TiO2 nanopowder was pasted on conducting surface of FTO glass slide by using doctor blade method and triton X-100 used as a binder. The optical properties of the natural dyes were also investigated and present work aqueous lugol's iodine was used as electrolyte. The 1:1 ratio of Chlorophyll and betalain dye mixer was used as a sensitizer in NDSSC and shown solar cell efficiency about 0.11% was achieved under one sun solar simulator (1.5 AMG).